1997
DOI: 10.3171/jns.1997.87.6.0830
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cerebral vasospasm after endovascular treatment of acutely ruptured aneurysms: report on 69 cases

Abstract: Cerebral vasospasm is the most common cause of morbidity and mortality in patients admitted to the hospital after suffering aneurysmal subarachnoid hemorrhage (SAH). The early surgical removal of subarachnoid clots and irrigation of the basal cisterns have been reported to reduce the incidence of vasospasm. In contrast to surgery, the endovascular treatment of aneurysms does not allow removal of subarachnoid clots. In this study the authors measured the incidence of symptomatic vasospasm after early endovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(56 citation statements)
references
References 62 publications
4
52
0
Order By: Relevance
“…Although no adequate study has been conducted, TCD is thought to be valuable in the day-to-day evaluation of sSAH patients in VSP and to assess the effect and durability of neuroradiologic interventions. 100,101 TCD has been used to detect angiographic VSP following prophylactic transluminal balloon angioplasty in sSAH patients at high risk of developing VSP, 102 as a noninvasive surrogate endpoint, or to demonstrate biologic effects of treatments for vasoconstriction or VSP in uncontrolled trials of pharmacologic therapies for eclampsia and sSAH. [103][104][105][106] Data are insufficient to make a recommendation regarding the use and method(s) of autoregulation testing for prediction of the risk of delayed cerebral ischemia.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…Although no adequate study has been conducted, TCD is thought to be valuable in the day-to-day evaluation of sSAH patients in VSP and to assess the effect and durability of neuroradiologic interventions. 100,101 TCD has been used to detect angiographic VSP following prophylactic transluminal balloon angioplasty in sSAH patients at high risk of developing VSP, 102 as a noninvasive surrogate endpoint, or to demonstrate biologic effects of treatments for vasoconstriction or VSP in uncontrolled trials of pharmacologic therapies for eclampsia and sSAH. [103][104][105][106] Data are insufficient to make a recommendation regarding the use and method(s) of autoregulation testing for prediction of the risk of delayed cerebral ischemia.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…Symptomatic vasospasm is reported in 22-40% of patients with SAH, resulting in 34% morbidity and 30% mortality rates. [27][28][29][30][31] Murayama et al 32 reported a 23% incidence of symptomatic vasospasm after endovascular coil occlusion of acutely ruptured; this rate compares favorably with that found in conventional surgical series. Gruber et al 33 , however, noted an increased incidence of vasospasm-related infarctions in patients treated endovascularly (37.7% vs. 21.6% with surgery).…”
Section: Ischemic Eventsmentioning
confidence: 48%
“…The theoretical advantage of the endovascular approach is that it allows early intervention and thus protection from rebleeding. The procedure avoids direct mechanical trauma to the brain and can be performed at any time, even during the acute phase or vasospasm, and it has been reported that treatment-related morbidity rates are less dependent on timing than are rates for conventional surgery [2,18,32]. Baltsavias et al [2] reported that the interval between endovascular treatment and SAH did not affect periprocedural morbidity rates and, therefore, that coil embolization should be performed as early as possible after SAH to prevent aneurysmal rerupture.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to surgical clipping, the endovascular approach does not allow removal of the subarachnoid clot, and it is unclear whether this limitation significantly affects the incidence of vasospasm. However, according to Murayama et al [18], who studied 69 patients who underwent occlusion of aneurysms via Guglielmi detachable coils within 72 hours of rupture, endovascular therapy did not have an unfavorable impact on cerebral vasospasm. Three patients suffered severe vasospasm in the present study, but the frequency and severity of vasospasm cannot be quantified with this small number of patients.…”
Section: Controversymentioning
confidence: 99%